Pengaruh Pendidikan Kewirausahaan, Inovasi, dan Etika Bisnis Islam terhadap Pemasaran Media Sosial pada Generasi Z yang Berperan sebagai Tiktok Affiliater - Irawan, Bambang; Ligery, Finny; Setiawan, Agus; Subandi, Subandi (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
The development of digital marketing through social media, particularly the TikTok Affiliate program, has created new entrepreneurial opportunities for Generation Z; however, it still faces challenges in terms of innovation and the implementation of Islamic business ethics. This study aims to analyze the influence of entrepreneurship education on social media marketing, both directly and through the mediating roles of innovation and Islamic business ethics. This research employs a quantitative explanatory approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected through closed-ended questionnaires from 250 Generation Z respondents aged 18–27 years who are active as TikTok Affiliates, and selected using purposive sampling. The findings indicate that entrepreneurship education has a positive and significant effect on innovation, Islamic business ethics, and social media marketing. In addition, innovation and Islamic business ethics are proven to act as mediating variables. These results emphasize the importance of integrating entrepreneurship education, innovation, and Islamic business ethics in developing digital marketing strategies that are effective, ethical, and sustainable.